A Study of Factors Affecting Consumer Behavioural Intentions Towards Adoption of Gamification - Gupta, Rajni; Mathad, Kavita (Indian Journal of Marketing, 2017)
Advanced technology with a high degree of accessibility of the Internet across countries has led to the emergence of e-commerce and m-commerce. The global brands and the start-ups are equally attracted to this change in the way the goods and services can be marketed, making market access through the Internet a core part of the strategy for marketers. The same has led to various digital promotional techniques for customer engagement. Among various digital promotional techniques, gamification is one technique where customers are expected to play online games to win the reward points for getting discounts for their purchases. An attempt was made to identify various factors influencing the consumer behavioural intentions towards adoption of gamification as one of the means to get products at discounted prices. In this study, factor analysis was used to find the major factors that influence the consumer behavioural intentions to adopt gamification as one of the digital promotional techniques. The study found eight major factors that influence the adoption of gamification, they are Personal Perspective, Usefulness, Easy to Use, Price Consciousness, Perceived Critical Mass, Flow Experience, Awareness, and Personal Innovativeness. This study brought in a different perspective by exploring the role of possible factors influencing gamification adoption in the Indian market, helping marketers, the major factors, and their influence on the consumer's behavioural intentions of adoption of gamification as one of the digital promotion techniques.